Carga Mental y Síndrome de Burnout en los Colaboradores de una Empresa Pública de Movilidad - Cárdenas Araque, Andrea Noemy (2022)
The present titling work was carried out in the Public Mobility Company of the Commonwealth of Cotopaxi, with the objective of determining the relationship between Mental Load and Burnout Syndrome in the employees of the Public Mobility Company of the Commonwealth of Cotopaxi. , through evaluations of the dimensions that will emerge in the evaluation instruments. The instruments used were the Questionnaire for mental workload assessment & Maslach Burnout Inventory, and whose instruments were applied to 66 employees of the company. The descriptive and correlational analyzes were carried out using the SPSS 22 program. The results confirmed the hypothesis that Burnout is correlated with mental load, since the levels of the syndrome were positively and significantly associated. The hypothesis test with Spearman's Rho showed a relationship between the two variables, therefore, a model was proposed for the analysis of mental load and burnout syndrome with the new components found such as: Physical / Emotional Exhaustion, Intrapersonal Motivation, Capabilities Cognitive, Investigative, Objectivity, Pressure, Projective, Assertiveness.